Ukraine : Second Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Second Review for Ukraine under the Stand-By Arrangement and request for modification of performance criteria. Policy implementation has been broadly in line with the program. The end-May quantitative performance criteria on base money, net international reserves, and the general government balance were met. The authorities made progress in the resolution of systemic problem banks and in preparing associated legislative actions. IMF staff welcomes the recent measures to improve the functioning of the foreign exchange market.